2020
DOI: 10.35940/ijmh.a1123.095120
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Organizational Culture, Organizational Justice, and Organizational Commitment on Organizational Citizenship Behavior (OCB)

Abstract: Organizational citizenship behavior (OCB), which is known as extra-role behavior, is an important factor for the organization to maintain the survival and achievement of organizational goals. OCB is very effective to be applied in human resource management because it can direct employees to provide performance that is more than just carrying out their formal duties. This study aimed to determine the influence of organizational culture, organizational justice, and organizational commitment to employee OCB at a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 7 publications
1
6
0
2
Order By: Relevance
“…A high level of commitment will make someone give their best effort when completing their tasks. This is in accordance with the findings of Winarsih & Riyanto that when an employee feels that the company has become their home, contributes greatly to their lives and provides a pleasant experience, it will improve the employee's good relationship with his co-workers (Winarsih & Riyanto, 2020).…”
Section: Organizational Commitmentsupporting
confidence: 92%
“…A high level of commitment will make someone give their best effort when completing their tasks. This is in accordance with the findings of Winarsih & Riyanto that when an employee feels that the company has become their home, contributes greatly to their lives and provides a pleasant experience, it will improve the employee's good relationship with his co-workers (Winarsih & Riyanto, 2020).…”
Section: Organizational Commitmentsupporting
confidence: 92%
“…Mani and Manida (2020) showed that high remuneration, promotion, good pension scheme, job security, and recognition are motivational factors that make employees more satisfied. The other opinions also state that the reward policy is a component of motivational factors that can avoid the emergence of job dissatisfaction by employees (Wasiman, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Rewards encourage employees to increase their work performance (Wasiman, 2020). They can be divided into intrinsic and extrinsic (Gautam, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Penelitian ini sejalan dengan hasil penelitian yang dilakukan oleh Wahyuni dan Supartha (2019) yang menjelaskan keadilan organisasional berpengaruh positif dan signifikan terhadap OCB. (Winarsih & Riyanto, 2020) yang menjelaskan organizational justice had a positive and significant effect on OCB.…”
Section: Pengujian Terhadap Hipotesis Dalam Penelitian Ini Menggunaka...unclassified